(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The article presents the results of experimental research on the effect of the amount of basalt fiber on the physical and mechanical properties of fine-grained concrete. The selected composition of micro-reinforced sandy concrete is recommended for the manufacture of thin-walled spatial structures. Conclusions on the research work carried out are presented.